Phytochemical and pharmacological evaluation of Vanda tricolor from Gumitir, East Java, Indonesia - FUAD BAHRUL ULUM; YUSI ANANDA PUTRI; ABDILLAH MAULANA FARHAN; DWI SETYATI; RANJITHKUMAR RAJAMANI; BAMBANG SUGIHARTO; MUKHAMAD SU’UDI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ulum FB, Putri YA, Farhan AM, Setyati D, Rajamani R, Sugiharto B, Su’udi M. 2025. Phytochemical and pharmacological evaluation of Vanda tricolor from Gumitir, East Java, Indonesia. Biodiversitas 26: 4783-4792. Vanda tricolor an epiphytic orchid native to the coffee agroforest of Gumitir, East Java, Indonesia, represents a promising source of pharmacologically active compounds. This study aimed to characterize the bioactive constituents of V. tricolor and evaluate their antioxidant, antimicrobial, and anticancer potential. Methanolic leaf extracts were analyzed using gas chromatography-mass spectrometry (GC-MS) for metabolite profiling. Its biological activities were assessed through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, agar well diffusion method, and molecular docking against the antiapoptotic Bcl-2 protein. GC-MS analysis identified 48 metabolites, with 4-butylphenol (7.57%) as the predominant compound. The extract demonstrated very strong antioxidant activity (IC??: 37.25 ppm), along with moderate antibacterial effects against Staphylococcus aureus and Escherichia coli; however, it showed no growth inhibition against Salmonella typhi. Molecular docking revealed that 4-butylphenol exhibited the highest binding affinity toward Bcl-2 (-5.50 kcal/mol), indicating its potential as a lead compound for anticancer therapy. These findings represent the first integrated phytochemical and pharmacological profile of V. tricolor from Gumitir, underscoring its value as a source of natural bioactive agents. The results also provide a scientific basis for further exploration of orchids in drug discovery and contribute to the conservation of this underutilized native species.